Pengelolaan Sumber Daya Alam dan Keuangan Keluarga Untuk Kepemilikan Harta Benda (Kekayaan) - Sandag, Marseni (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2020)
Work as a farmer is interpreted as an activity to earn a living daily and as the most realistic way of life in a rural environment. Actually, rural areas have the potential for abundant natural resources, but they have not been fully utilized. The development of potential natural resources and human resources is still very minimal. The two resources must support and complement each other. The reality is that some churches only want to see themselves without caring about every problem the congregation has in managing family finances. The fact that exists in church life is that there are still various complaints and struggles from church members regarding the economic condition of the congregation to manage natural resources and finances in order to obtain wealth that can be used to meet present and future needs and to support service programs in the church.